2011
DOI: 10.1038/onc.2011.180
|View full text |Cite
|
Sign up to set email alerts
|

Integrative mRNA profiling comparing cultured primary cells with clinical samples reveals PLK1 and C20orf20 as therapeutic targets in cutaneous squamous cell carcinoma

Abstract: Identifying therapeutic targets for cancer treatment relies on consistent changes within particular types or sub-types of malignancy. The ability to define either consistent changes or sub-types of malignancy is often masked by tumor heterogeneity. To elucidate therapeutic targets in cutaneous squamous cell carcinoma (cSCC), the most frequent skin neoplasm with malignant potential, we have developed an integrated approach to gene expression profiling beginning with primary keratinocytes in culture. Candidate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 52 publications
10
71
0
Order By: Relevance
“…Consistent with our immunofluorescence data, analysis of our previous microarray data 34 showed that CARD11 mRNA expression was increased in primary cultured cSCC keratinocytes compared with normal primary keratinocytes and significantly increased in cSCC tissue compared with normal skin (P Z 0.0067). CARD14 expression was comparable with CARD11 in vitro and in vivo but was not altered in cSCC ( Figure 4B).…”
Section: Card11 Mrna Expression Is Increased In Cscc Compared With Nosupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our immunofluorescence data, analysis of our previous microarray data 34 showed that CARD11 mRNA expression was increased in primary cultured cSCC keratinocytes compared with normal primary keratinocytes and significantly increased in cSCC tissue compared with normal skin (P Z 0.0067). CARD14 expression was comparable with CARD11 in vitro and in vivo but was not altered in cSCC ( Figure 4B).…”
Section: Card11 Mrna Expression Is Increased In Cscc Compared With Nosupporting
confidence: 89%
“…Each show increased proliferation, inflammation, and delayed differentiation, however, cSCC is malignant and psoriasis benign. We and others have exploited these properties to identify gene expression changes specific to cSCC, 34,41 and it is tempting to speculate that at least some of the differences between these two diseases may be mediated through differential CARD signal transduction. It is important to note that CARD scaffold proteins can signal through pathways other than NF-kB, such as Jun N-terminal kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the introduction, various independent studies conducted thus far have revealed heterogeneity in the incidence of RAS mutations in human cSCC and we have been unable to detect RAS mutations in six RDEB SCC patients and four non-RDEB SCC patient samples (Pourreyron et al, 2007). Similar to non-RDEB SCC data a proportion of RDEB tumours harbour TP53 mutation and CDKN2A methylation/ aberrant expression (Arbiser et al, 2004;Watt et al, 2011). In the following section we discuss the various ideas and studies investigating aspects of RDEB and RDEB SCC pathology.…”
Section: Search For Mechanisms Involved In Rdeb Scc Tumourigenesismentioning
confidence: 59%
“…To date no single study has identified a distinct difference in the histology or expression of markers both at the mRNA or protein level when comparing cSCC from RDEB patients with cSCC in the general population. We have recently tried to address this question with a gene expression study utilising microarrays containing more than 47,000 probes to interrogate RNA isolated from primary cSCC keratinocytes isolated from RDEB and non-RDEB patients (Watt et al, 2011).…”
Section: Are There Differences Between Rdeb Scc and Non-rdeb Scc?mentioning
confidence: 99%